2015
DOI: 10.3892/ol.2015.3647
|View full text |Cite
|
Sign up to set email alerts
|

The role and mechanism of WEE1 on the cisplatin resistance reversal of the HepG2/DDP human hepatic cancer cell line

Abstract: Abstract. Drug resistance to cisplatin with continuous drug treatment is one of the most common causes of chemotherapy failure in hepatic carcinoma. Accumulating evidence suggests that WEE1 G2 checkpoint kinase (WEE1) is involved in cisplatin resistance, which has been demonstrated to correlate with cancer initiation and progression. However, the role and molecular mechanism of WEE1 in the drug resistance of hepatic cancer remains unclear. In the present study, using the WEE-knockdown hepatic cancer cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Liu et al (26) found that high-mobility group box 1 protein (a regulator of autophagy) was released in colorectal cancer cell lines following chemotherapy with oxaliplatin and decreased the sensitivity of colorectal cancer cells to oxaliplatin by activating the MEK/ERK pathway. Zhao et al (27) confirmed that silencing WEE1 expression reversed multidrug resistance and increased the sensitivity of HepG2/DDP cells to cisplatin. The underlying mechanism was associated with inhibition of the MAPK/ERK signaling pathway and the downregulated expression of genes that are associated with multidrug resistance.…”
Section: Discussionmentioning
confidence: 94%
“…Liu et al (26) found that high-mobility group box 1 protein (a regulator of autophagy) was released in colorectal cancer cell lines following chemotherapy with oxaliplatin and decreased the sensitivity of colorectal cancer cells to oxaliplatin by activating the MEK/ERK pathway. Zhao et al (27) confirmed that silencing WEE1 expression reversed multidrug resistance and increased the sensitivity of HepG2/DDP cells to cisplatin. The underlying mechanism was associated with inhibition of the MAPK/ERK signaling pathway and the downregulated expression of genes that are associated with multidrug resistance.…”
Section: Discussionmentioning
confidence: 94%
“…We have testified that HJURP could modulate MYC/WEE1 axis and MYC was an upstream transcription factor of WEE1. Considering that WEE1 inhibitor could synergize with many DNA damage agents including cisplatin [31][32][33][34][35], we would like to explore whether MYC/WEE1 axis was the intermediate process of chemoresistance induced by HJURP. As shown in Supplementary Figures S5A, B, clonogenic formation number increased in HJURP overexpression group compared with control at 2μg/ml concentration of cisplatin in SKOV3.…”
Section: Hjurp Modulates Cisplatin Chemoresistance In Ovarian Cancer Through Myc/wee1 Axismentioning
confidence: 99%
“…The synergistic lethality phenomenon indicated WEE1 could be a novel therapeutic target in combinatory strategies containing DNA-damaging agents. Various studies indicated that WEE1 could modulate cisplatin sensitivity by multiple mechanisms and targeting WEE1 was promising for overcoming cisplatin resistance [33][34][35]. Besides, WEE1 could also inactivate CDK2 during S phase, performing maintenance of replication forks and controlling genomic stability [36][37][38].…”
Section: Introductionmentioning
confidence: 99%